1999
DOI: 10.1080/026404199366145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endurance training on blood lactate clearance after maximal exercise

Abstract: The aim of this study was to measure serial changes in the rate of blood lactate clearance (gamma2) in response to sequential periods of training and detraining in four male triathletes aged 22-44 years. There were two major phases of training and taper, each lasting 4-5 weeks (training 1 = 5 weeks, taper 1 = 2 weeks, training 2 = 4 weeks and taper 2 = 2 weeks), in preparation for a triathlon competition. The training stimulus absorbed by each subject was carefully quantified from the duration and intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Georges Brooks' group have demonstrated that endurance training enhanced the whole body and leg lactate clearance at a high relative power output [5,20]. This had already been reported by Fukuba et al [22] who measured the kinetics of the blood lactate after a 30 W min -1 ramp cycle ergometer test to exhaustion. Marathoners performed many long -slow distance runs in winter and they probably had already enhanced their lactate clearance.…”
Section: Trainingmentioning
confidence: 60%
“…Georges Brooks' group have demonstrated that endurance training enhanced the whole body and leg lactate clearance at a high relative power output [5,20]. This had already been reported by Fukuba et al [22] who measured the kinetics of the blood lactate after a 30 W min -1 ramp cycle ergometer test to exhaustion. Marathoners performed many long -slow distance runs in winter and they probably had already enhanced their lactate clearance.…”
Section: Trainingmentioning
confidence: 60%
“…[86] Although the greater 'fatigue resistance' of better distance athletes is not well-understood, [86,87] superior endurance performances may be related to lower rates of lactate accumulation in working muscles. [72,81,[88][89][90][91][92][93] In highly trained endurance athletes, there is little increase in plasma lactate concentration with increasing work rates [41] until exercise intensity reaches 80 to 85% of V . O 2peak .…”
Section: Effects Of Sustained High-intensity Interval Training In Welmentioning
confidence: 99%
“…The horses investigated in our study usually were walked during the first 30 minutes of recovery. The ability to remove lactate is directly associated with the oxidative capacity of muscle fibers and it has been shown that the rate of lactate disappearance increases with training . Horses competing at higher level therefore may have been able to remove lactate at a higher rate compared to those competing at lower level as a result of higher oxidative capacity of their muscles.…”
Section: Discussionmentioning
confidence: 99%